2004
DOI: 10.1152/ajpregu.00140.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligodeoxynucleotides directed against a novel angiotensinogen mRNA-stabilizing protein reduce blood pressure in spontaneously hypertensive rats

Abstract: We have previously reported that hypertension in the young spontaneously hypertensive rat (SHR) is associated with an elevation in tissue angiotensinogen and a novel polysomal protein known to stabilize angiotensinogen mRNA. In our current study we determined the role of the mRNA-stabilizing protein in the regulation of tissue angiotensinogen expression and mean arterial pressure (MAP) in the SHR utilizing antisense oligodeoxynucleotide (AON) inhibition. Three AONs (RNASTAAS1, position 31-50; RNASTAAS2, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Importantly, antihypertensive effects after blockade of Aogen mRNA synthesis were similar to those observed after inhibition of the RAS by converting enzyme inhibitor or AT 1 receptor blockade. 32 These observations, together with those of the present study, showed clearly that training caused a similar antihypertensive effect as the pharmacological therapies and strongly suggest that reduced Aogen expression within brain stem areas controlling cardiovascular function is involved in the mediation of the response. If a similar deactivation also occurs in other brain areas, such as the hypothalamic integrative centers, it remains to be determined.…”
Section: Felix and Michelini Exercise Training And Brain Ras 783supporting
confidence: 85%
See 2 more Smart Citations
“…Importantly, antihypertensive effects after blockade of Aogen mRNA synthesis were similar to those observed after inhibition of the RAS by converting enzyme inhibitor or AT 1 receptor blockade. 32 These observations, together with those of the present study, showed clearly that training caused a similar antihypertensive effect as the pharmacological therapies and strongly suggest that reduced Aogen expression within brain stem areas controlling cardiovascular function is involved in the mediation of the response. If a similar deactivation also occurs in other brain areas, such as the hypothalamic integrative centers, it remains to be determined.…”
Section: Felix and Michelini Exercise Training And Brain Ras 783supporting
confidence: 85%
“…Together these observations reinforce the importance of an overactive brain RAS to condition elevated blood pressure in hypertension and the proposition that blockade of brain and/or plasma Aogen is essential for pressure fall in hypertensive individuals. 30,32 The present experimental evidence, showing positive significant correlations between NTS Aogen mRNA expression and MAP levels in the SHR (but not in the WKY group) and in the sedentary rats (not trained; Figure 2A and 3A, respectively), reinforces the association between blood pressure and brain Aogen content, suggesting additionally an important effect of training on them. Previous studies have already shown that hypertension coexists with high Ang II levels in brain areas involved in cardiovascular control.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has also been shown that converting enzyme inhibitors, as well as angiotensin receptor blockers, reduced the collagen/elastin ratio in treated SHR while attenuating the expression of integrin in the arteries [12,14,36]. Indeed, exercise training by reducing either the activity of the renin-angiotensin system [37,38], mean pressure and pulsatility (present set of data) was able to decrease aortic stress and the stress-sensing mechanism. Future experiments might explore these possibilities.…”
Section: Discussionmentioning
confidence: 61%
“…Although the modulation of plasma renin is generally considered to be the primary regulator of the renin–angiotensin system (RAS), experiments in laboratory animals have demonstrated that the circulating or tissue level of AGT may also be important in the regulation of the RAS. Studies in the spontaneously hypertensive rat demonstrated that antisense inhibition of an AGT mRNA‐stabilizing protein leads to a reduction in arterial blood pressure (Klett et al 2004). Moreover, intrarenal AGT mRNA and protein (Kobori et al 2001 a ; Kobori et al 2001 b ) levels are increased in experimental angiotensin (ANG) II‐induced hypertension in rats, indicating both a role of AGT in hypertension and a potential feed‐forward effect of ANG II on AGT.…”
mentioning
confidence: 99%